The Effect of Quality of Work Life (QWL) and Workload of Employees at Class II Kijang Port Offices and Port Authority Offices - Nurhasanah Nurhasanah; Kiki Wulandari; Astuti Astuti (Kusuma Negara Business School, 2022)
This study aims to determine and analyze whether there is an effect of quality of work life and workload on employee job satisfaction at Office X. This study is categorized as a quantitative study with an instrument in the form of a questionnaire. The population in this study were all 41 employees of Office X. The sampling technique is by means of a saturated sampling technique or a census. The sample in this study is to take the population or as many as 41 samples. The data used in this study is primary data obtained through a questionnaire. The instrument validity test used the Bivariate Correlation formula, while the reliability test used Cronbach Alpha. The measuring instrument proved to be valid and reliable for the research instrument. Multiple regression analysis was used to test the hypothesis of this study. Based on the results of this study, it is known that the results of the multiple linear regression test are Y = 2.826 + 0.16 X1 + 1.082 X2, where Quality Of Work Life (X1), Workload (X2), and Personnel Performance (Y). Then the T test results of the Quality Of Work Life variable have no significant effect on employee job satisfaction (1,488 < 1,68288). The workload has a significant effect, namely (22.009 > 1.6828. The F test together has a significant effect on employee job satisfaction (247.626 > 2.85). The results of the R square test give a value of 0.925, which means 92.5% of the job satisfaction variable employees can be explained through the two independent variables, while the remaining 7.5% is influenced or explained by other factors not included in this study.